Angiotensin II Type 2 Receptor Decreases Transforming Growth Factor-β Type II Receptor Expression and Function in Human Renal Proximal Tubule Cells - Guo, Hui-Lin (PLoS One, 2016)
Transforming growth factor-β (TGF-β), via its receptors, induces epithelial-mesenchymal transition (EMT) and plays an important role in the development of renal tubulointersitial fibrosis. Angiotensin II type 2 receptor (AT(2)R), which mediates beneficial renal physiological functions, has received attention as a prospective therapeutic target for renoprotection. In this study, we investigated the effect and underlying mechanism of AT(2)R on the TGF-β receptor II (TGF-βRII) expression and function in human proximal tubular cells (HK-2). Here, we show that the AT(2)R agonist CGP42112A decreased TGF-βRII protein expression in a concentration- and time-dependent manner in HK-2 cells. The inhibitory effect of the AT(2)R on TGF-βRII expression was blocked by the AT(2)R antagonists PD123319 or PD123177. Stimulation with TGF-β1 enhanced EMT in HK-2 cells, which was prevented by pre-treatment with CGP42112A. One of mechanisms in this regulation is associated with the increased TGF-βRII degradation after activation of AT(2)R. Furthermore, laser confocal immunofluorescence microscopy showed that AT(2)R and TGF-βRII colocalized in HK-2 cells. AT(2)R and TGF-βRII coimmunoprecipitated and this interaction was increased after AT(2)R agonist stimulation for 30 min. The inhibitory effect of the AT(2)R on TGF-βRII expression was also blocked by the nitric oxide synthase inhibitor L-NAME, indicating that nitric oxide is involved in the signaling pathway. Taken together, our study indicates that the renal AT(2)R regulates TGF-βRII expression and function via the nitric oxide pathway, which may be important in the control of renal tubulointerstitial fibrosis.